Genetic diversity and population structure analysis of 418 tomato cultivars based on single nucleotide polymorphism markers - Xu, Weijie; Gong, Chao; Mai, Peiting; Li, Zhenxing; Sun, Baojuan; Li, Tao (Frontiers in Plant Science, 2024)
Introduction Tomato (Solanum lycopersicum) is a highly valuable fruit crop. However, due to the lack of scientific and accurate variety identification methods and unified national standards, production management is scattered and non-standard, resulting in mixed varieties. This poses considerable difficulties for the cataloging and preservation of germplasm resources as well as the identification, promotion, and application of new tomato varieties. Methods To better understand the genetic diversity and population structure of representative tomato varieties, we collected 418 tomato varieties from the past 20 years and analyzed them using genome-wide single nucleotide polymorphism (SNP) markers. We initially assessed the population structure, genetic relationships, and genetic profiles of the 418 tomato germplasm resources utilizing simplified genome sequencing techniques. A total of 3,374,929 filtered SNPs were obtained and distributed across 12 chromosomes. Based on these SNP loci, the 418 tomatoes samples were divided into six subgroups. Results The population structure and genetic relationships among existing tomato germplasm resources were determined using principal component analysis, population structure analysis, and phylogenetic tree analysis. Rigorous selection criteria identified 15 additional high-quality DNA fingerprints from 50 validated SNP loci, effectively enabling the identification of the 418 tomato varieties, which were successfully converted into KASP (Kompetitive Allele Specific PCR) markers. Discussion This study represents the first comprehensive investigation assessing the diversity and population structure of a large collection of tomato varieties. Overall, it marks a considerable advancement in understanding the genetic makeup of tomato populations. The results broadened our understanding of the diversity, phylogeny, and population structure of tomato germplasm resources. Furthermore, this study provides a scientific basis and reference data for future analysis of genetic diversity, species identification, property rights disputes, and molecular breeding in tomatoes.